EFEKTIVITAS IMPLEMENTASI KEBIJAKAN AKUN BELAJAR.ID KEMENDIKBUD OLEH TENAGA KEPENDIDIKAN - Wahyudi, Dudi; Suwandana, Endan (Jurnal Kebijakan Pembangunan Daerah, 2022)
ABSTRACT The purpose of this study is to determine the effectiveness of the implementation of the Secretary General of the Ministry of Education and Culture policy which regulates the use of belajar.id accounts by the education personnel. The respondents of this study are school supervisors, principals, teachers and other education personnel throughout Indonesia with a total of 514 respondents with the largest portion of respondents (52.2%) from Banten Province. The method used in this study is survey method with questionnaire and written interview via Google Form. The interesting finding of this study is that the implementation of belajar.id policy has been effectively undergoing, as that proved with the following facts: (1) The majority of respondents have utilized belajar.id account for their daily activities, with varying frequency of use; (2) The use of belajar.id accounts is not only focused on one tool, but varied on three tools, i.e. Google Classroom, Google Form and Google Meet; (3) Training on the use of belajar.id accounts is obtained from Google Masters, colleagues, and others. Support from the government is still needed to further broaden the use of belajar.id accounts, since there are still respondents who have not received training on belajar.id accounts. Keywords: Evaluation of education policy, online learning, educational technology